Means of communication in crisis management at Sonelgaz Constantine 02 - naili, khaled; bouchareb, khaled (Journal of Social Sciences and Humanities, 2022)
Through this research document, we will try to discover the different means of communication and the modern information and communication technologies that Sonelgaz Constantine 02 uses to manage the crises that it encounters from time to time. Where we relied on the descriptive approach, which is based on the explanation of the phenomenon in order to conclude a precise and complete practical description of the crisis based on the associated facts. We also used the questionnaire as a basic tool for data collection. In the end, we have come to the fundamental conclusion that the institution depends on certain modern information and communication means and technologies, but neglects others.